PEMBANGUNAN MANUSIA KOTA SEMARANG, ANTARA CAPAIAN DAN TANTANGAN - Lilis Anisah (Badan Perencanaan Pembangunan Daerah Kota Semarang, 2019)
This paper studies the achievements and challenges of Semarang City's human development through several indicators available in the 2013-2017 period. The results show that the achievements of Semarang City HDI were quite encouraging. Since 2015 Semarang City HDI has exceeded index 80, precisely 80.23. This condition increases the classification of Semarang City HDI from the high category of HDI classification to the very high one. Semarang's HDI also always surpasses the Central Java and National HDI Provinces. Another achievement is that the Semarang City HDI occupies the highest position for the City Regency in Central Java in the last two years. Compared to the Provincial Capital in Java Island, the highest status of the Semarang City HDI has only been surpassed by Yogyakarta City since 2014. Such condition is an important capital for the Semarang City to face challenges in increasing the future human development.Challenges faced by Semarang City related to human development include aspects of health, education and the economy. In addition to describing the achievements of human development, this study will descriptively depict the challenges of human development in Semarang City based on indicators that are relevant to those three aspects. The data used in this study are taken from Central Statistics Agency (BPS) in the form of National Socio-Economic Survey (Susenas) data, National Labor Force Survey (Sakernas) data and Semarang City Health Office data. All those data have speeded up the improvement of the human development quality in Semarang City.